Archaeobotanical Approaches in the Study of Food Production in Remote Oceania - Levin, Maureece Jacqueline (Ethnobiology Letters, 2017)
This short topical review discusses recent archaeobotanical approaches to understanding food production in Remote Oceania (eastern Melanesia, Micronesia, and Polynesia). The region presents some preservation and interpretative challenges, both due to the lack of cereal crops and the hot and humid climate that prevails through much of the area. Nevertheless, archaeobotanical analyses provide insight into topics such the transport of crops between islands and anthropogenic environmental change.